Building an Ommatidium One Cell at a Time - Kumar, Justin P. (2012)
Since the discovery of a single white eyed male in a population of red eyed flies over 100 years ago (Morgan, 1910), the compound eye of the fruit fly, Drosophila melanogaster, has been a favorite experimental system for identifying genes that regulate various aspects of development. For example, a fair amount of what we know today about enzymatic pathways and vesicular transport is due to the discovery and subsequent characterization of eye color mutants such as white. Likewise, our present day understanding of organogenesis has been aided considerably by studies of mutations, such as eyeless, that either reduce or eliminate the compound eyes. But by far the phenotype that has provided levers into the greatest number of experimental fields has been the humble “rough” eye. The fly eye is comprised of several hundred unit-eyes that are also called ommatidia. These unit eyes are packed into a hexagonal array of remarkable precision. The structure of the eye is so precise that it has been compared to that of a crystal (Ready et al., 1976). Even the slightest perturbations to the structure of the ommatidium can be visually detected by light or electron microscopy. The cause for this is two-fold: (1) any defect that affects the hexagonal geometry of a single ommatidium can and will disrupt the positioning of surrounding unit eyes thereby propagating structural flaws and (2) disruptions in genes that govern the development of even a single cell within an ommatidium will affect all unit eyes. In both cases the effect is the visual magnification of even the smallest imperfection. Studies of rough eye mutants have provided key insights into the areas of cell fate specification, lateral inhibition, signal transduction, transcription factor networks, planar cell polarity, cell proliferation and programmed cell death just to name a few. This review will attempt to summarize the key steps that are required to assemble each ommatidium.